UNVEILING THE ESSENCE OF WORLDLY LIFE THROUGH THE PERSPECTIVE OF TASAWUF IRFANI: A STUDY ON ITS IMPLICATIONS FOR INDONESIAN URBAN MUSLIM SOCIETY - Ulfa, Fadillah; Mukhlizar, Mukhlizar; Zarrina Sa'ari, Che; Rahman, Syed Mohammad Hilmi Syed Abdul (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
This study examines the essence of world life through Tasawuf Irfani, which emphasizes intellectual understanding of divine knowledge and soul purification. It explores how these teachings shape Indonesian Muslims' perspectives on materialism, wealth, and life's true purpose. The study emphasizes the increasing focus on how Tasawuf Irfani tackles materialism, consumerism, and spiritual fulfillment, while existing literature mainly explores its philosophical aspects, neglecting its practical implementation in Indonesian society. This qualitative study uses literature review and textual analysis to explore Tasawuf Irfani’s teachings, Islamic views on worldly life, and their impact on socio-economic behaviors, focusing on the balance between material success and spiritual growth in Indonesia. The results reveal that Tasawuf Irfani provides a profound critique of materialism and consumerism, encouraging Indonesian Muslims to view wealth and worldly success as tools for spiritual growth rather than ultimate goals. It also fosters qualities such as humility, moderation and social responsibility. On the other hand, the study points out challenges like the risk of overly disengaging from material pursuits, which may result in limited involvement with pressing social issues in a pragmatic sense. Tasawuf Irfani concludes with a spiritually based perspective concerning wealth and success, suggesting potential integration within education and community initiatives to alleviate socio-economic issues in Indonesia, which can be the focus of future research.